Copper nanoparticle-induced ovarian injury, follicular atresia, apoptosis, and gene expression alterations in female rats - Yang J (Dove Medical Press, 2017)
Jing Yang,1,* Shifu Hu,1,* Meng Rao,1 Lixia Hu,2 Hui Lei,1 Yanqing Wu,1 Yingying Wang,1 Dandan Ke,1 Wei Xia,1,3 Chang-hong Zhu1,3 1Family Planning Research Institute, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei, 2Department of Histology and Embryology, Preclinical Medicine College, Xinxiang Medical University, Henan Province, Xinxiang, 3Reproductive Medicine Center, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei, People’s Republic of China *These authors contributed equally to this work Abstract: Numerous studies have reported the accumulation of copper nanoparticles (Cu NPs) in organs and the corresponding damage, although whether Cu NPs can be translocated to the ovaries and their ovarian toxicity are still unknown. In this study, three groups of female rats were injected with 3.12, 6.25, or 12.5 mg/kg Cu NPs for 14 consecutive days. The pathological changes, hormone levels, apoptosis and apoptotic proteins, oxidative stress, and gene expression characteristics in the ovaries were then investigated. The results demonstrated that the Cu NPs exhibited obvious accumulation in the rat ovaries, leading to ovarian injury, an imbalance of sex hormones, and ovarian cell apoptosis. Cu NP exposure activated caspase 3, caspase 8, caspase 9, and tBid, decreased the protein levels of Bcl-2, increased the expression levels of the proteins Bax and cytochrome c, and promoted malondialdehyde (MDA) accumulation and superoxide dismutase (SOD) reduction. Furthermore, gene microarray analysis showed that Cu NPs (12.5 mg/kg/d) caused 321 differentially expressed genes. Of these, 180 and 141 genes were upregulated and downregulated, respectively. Hsd17b1, Hsd3b1, Hsd3b6, and Hsd3b were involved in steroid and hormone metabolism, whereas Mt3 and Cebpb were associated with apoptosis. Overall, these findings provide strong evidence that Cu NPs trigger both intrinsic and extrinsic apoptotic pathways and regulate key ovarian genes in oxidative stress-mediated ovarian dysfunction. Keywords: Cu NPs, apoptosis, oxidative stress, microarray